An anti-inflammatory molecular mechanism of action of α-mangostin, the major xanthone from the pericarp of Garcinia mangostana: an in silico, in vitro and in vivo approach. Issue 7 (28th June 2018) - Mohan, Syam; Syam, Suvitha; Abdelwahab, Siddig Ibrahim; Thangavel, Neelaveni
Abstract : α-Mangostin (αMN) is a xanthone present in the pericarp of Garcinia mangostana Linn. Abstract : α-Mangostin (αMN) is a xanthone present in the pericarp of Garcinia mangostana Linn. which is mentioned in Ayurveda and is a widely used functional food supplement. However, its anti-inflammatory mechanism is not well studied. Hence, we used in silico, in vitro and in vivo models to provide information of the mechanism on how αMN could prevent inflammation. Firstly, molecular docking was used to find out the binding energy of αMN with NFκB and COX proteins. Secondly, LPS induced RAW 264.7 cells were used to measure the production of cytokines, the prevention of translocation of NFκB and the inhibition of COX-1 and -2 enzymes. Finally, carrageenan-induced peritonitis was used in vivo to check cytokine release, leukocyte migration and vascular permeability. The in silico modelling had showed that αMN has the lowest binding energy with COX-2 and NFκB proteins. αMN has been found to inhibit the production of PGE2 and nitric oxide, and iNOS protein expression. TNF-α and IL-6 cytokines were inhibited significantly ( p < 0.05) at 8 and 14 μg ml −1 concentration. αMN at higher doses inhibits the translocation of NFκB together with suppressing the COX-2 enzymes, but not COX-1. αMN inhibited the total leukocyte migration, predominantly, neutrophils in vivo . The level of TNFα and IL-1β was significantly ( p < 0.05) reduced in the peritoneal fluids as measured by ELISA analysis. Taken together, these results demonstrate that αMN acts well as an anti-inflammatory agent via inhibiting the hallmark mechanisms of inflammation. It can be considered as a potential alternative lead compound. In addition, the current results support the traditional use of this fruit pericarp as a functional food.